Analisis Delay Time Alat Angkut untuk Mengurangi Antrian Timbangan dari 80 Menit Menjadi 20 Menit pada Kegiatan Pengangkutan Batubara pada PT. Saptaindra Sejati - Farid Nuruddin; Afni Nelvi; Ahmad Fadhly (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
At this time the delay time that occurs on the DT-30T conveyance is 174 minutes and the DT-40T is 188 minutes. The biggest cause of delay time is the queue at the scales, namely on the DT-30T it is 80 minutes and the DT-40T is 85 minutes, thus causing actual productivity. The DT-30T was only 5.6 tons/hour and experienced a production loss of 0.4 tons/hour and the actual productivity of the DT-40T was only 6.9 tons/hour and experienced a production loss of 1.1 tons/hour. The aim of this research is to analyze the amount of delay time, production loss before and after improving the queue on the scales and how to reduce the queue time for scales on the DT-30T and DT-40T transportation equipment After processing the data, we obtain the Delay time on the DT-30T transport equipment after repairs the weighing queue is 33 minutes and the DT-40T is 28 minutes. The actual production of DT-30T after improvements to the weighing queue was 7 tons/hour and there was no production loss. Meanwhile, the actual production of the DT-40T after repairs was 9 tons/hour and there was no production loss.